Java Programming : comprehensive - Farrell, Joyce (Cambridge : Course Technology, 1999)
Using Java as the language, readers are exposed to object-oriented programming concepts along with the Java syntax to implement them. No programming experience is assumed.
Keywords: Java Programming; Programming Languagese